2019
DOI: 10.1177/1090198119885433
|View full text |Cite
|
Sign up to set email alerts
|

What Young People Need to Make Better-Informed Decisions When Communicating With Digital Images: Implications for Mental Health and Well-Being

Abstract: Sixty-eight young people contributed to a Design Thinking Challenge created to elicit a better understanding of their electronic image-sharing experiences, the helpful and harmful consequences of image-sharing to adolescent mental health and safety, and promising interventions that allow young people to make more positive decisions and minimize their risks when sharing images through electronic devices. Through this collaborative group-based process, each co-design group engaged in a four-phase process to disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In a study on cancer screening, people with higher levels of education were found to be more likely to seek screening for cancer as well as more likely to follow the science in making treatment decisions (Lange, 2011). Education also helps users respond to issues as they arrive such as how to manage online interactions with peers (Cardoso et al, 2020). Users rely in part on their education for making better-informed decisions so those without enough education may be vulnerable depending on the complexity of their information needs.…”
Section: Making Better-informed Decisionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study on cancer screening, people with higher levels of education were found to be more likely to seek screening for cancer as well as more likely to follow the science in making treatment decisions (Lange, 2011). Education also helps users respond to issues as they arrive such as how to manage online interactions with peers (Cardoso et al, 2020). Users rely in part on their education for making better-informed decisions so those without enough education may be vulnerable depending on the complexity of their information needs.…”
Section: Making Better-informed Decisionsmentioning
confidence: 99%
“…In a study on cancer screening, people with higher levels of education were found to be more likely to seek screening for cancer as well as more likely to follow the science in making treatment decisions (Lange, 2011). Education also helps users respond to issues as they arrive such as how to manage online interactions with peers (Cardoso et al. , 2020).…”
Section: Information Practicesmentioning
confidence: 99%
“…The target populations involved were also diverse but were identified as being vulnerable in some way when using social media. For example, there were studies with young people exploring cyberbullying [76,94,97,106] and studies with older adults working on building their internet and social media confidence [69,70,87]…”
Section: Question 1: Peer-reviewed Academic Literature Investigating ...mentioning
confidence: 99%
“…A recent report states that in a Design Thinking Challenge about sixty-eight people who are young helped those to have a deeper grasp of their experiences in electronic imagesharing, the harmful as well as helpful of images sharing repercussions on the mental health of adolescents, and safety, and also the interferences which are promising that makes young people take positive decisions in minimizing the dangers they face when exchanging photographs via technology devices [19]. Android App COVID Tracker attacks using ransomware virus.…”
Section: Introductionmentioning
confidence: 99%